If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6 + 4c = 34 Solving 6 + 4c = 34 Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + 4c = 34 + -6 Combine like terms: 6 + -6 = 0 0 + 4c = 34 + -6 4c = 34 + -6 Combine like terms: 34 + -6 = 28 4c = 28 Divide each side by '4'. c = 7 Simplifying c = 7
| 0x=12 | | 10x+11=-9 | | 4y-3=2x | | 2g+6/7=20 | | 24=(b-3)+8 | | 9(x-8)+12=8(x+8)+10 | | X^2+x-2=4 | | K/3+4=7 | | y=2(y+8)-4y | | 9+2=78 | | Ln(-1.4)=0 | | 26-1(4x-11)=5(x-1)-6 | | X-38=21 | | -2y-16=-(2y-8) | | (-4)(-3)(-7)= | | 2x-4(x-2)=-9+2x+1 | | 5x+12=8x-6 | | 1-8(-6n+7)=233 | | -4-6x-6=-11-7x | | -4n-7=-28 | | 4x-9x+2x= | | 15x+2(16+x)=1120 | | 4(x+1)=6x-1 | | Y=-2x/5+5 | | 33-15= | | 1/4a+35/12=109/36 | | -6+(-5)+9= | | 5(z+6)= | | 4x^2-5x-6=11 | | 9=3v-6/4+5v-4/8 | | 8(x+10)=x*4x | | -3x-7=-6x+2 |